The Influence Of The Role Of Financial Literacy And Financial Discipline On Budgeting Skills - Sari, Ratna; Putri, Ririn Yuliani (Growth: Journal Management and Business, 2024)
This study aims to analyze the influence of financial literacy and financial discipline on budgeting skills. The ability to manage personal finances is an essential skill in today's era of globalization and digitalization. Financial literacy, which includes an understanding of basic financial management concepts such as budgeting, savings, investments, and debt control, plays a crucial role in helping individuals make wise financial decisions. Meanwhile, financial discipline focuses on the habit of monitoring expenses, complying with planned budgets, and conducting periodic evaluations of personal financial management. These two factors are key components in shaping effective budgeting skills, allowing individuals to organize, organize, and evaluate their budgets in a more planned and efficient manner. This study uses a quantitative approach with a survey method through the distribution of questionnaires to respondents. The causal associative research design was used to test the cause-and-effect relationship between financial literacy and financial discipline on budgeting skills. Data is collected directly through questionnaires arranged with relevant measurement scales for each variable. The determination of the sample is carried out by a purposive sampling technique that includes individuals with certain criteria, such as having experience in personal financial management. The results of the study show that financial literacy and financial discipline have a positive influence on budgeting skills. Individuals with good financial literacy tend to be more able to prepare effective budgets because of a better understanding of income planning, fund allocation, and financial resource management. On the other hand, financial discipline contributes to encouraging individuals to adhere to a pre-prepared budget and keep spending under control. The implications of this study emphasize the importance of financial education as an effort to improve people's financial literacy and encourage the habit of discipline in financial management. Educational institutions, organizations, and financial institutions are expected to play an active role in providing relevant educational programs to equip individuals with better budget management skills. With increased financial literacy and financial discipline, individuals will be better able to achieve their financial stability and financial goals in a sustainable manner.